Penerapan Pembelajaran Karya Seni Menempel ( Mozaik ) Menggunakan Biji-Bijian Siswa Kelas IV SDN 1 Cendono Kabupaten Kudus - Maqfiroh, Ary Delia; Aleansyah, Filyas; Askha, Ulin Nimmati Millati; Noviyanti, Putri Amelia (CV. ITTC INDONESIA, 2024)
This research was conducted because of the low level of student creativity, this can be seen from the behavior of students who still do not dare to express their creative ideas in the work they produce. In creating fine arts for elementary school children, the important thing in creative activities is the student's creativity in producing the work, not the quality of the work. masterpiece. Teachers must be able to provide motivation in order to develop students' creativity. In this research, researchers chose creative activities by using natural materials in the form of grains to make unique works that have their own charm. The subjects in this research were class IV students at SDN 1 CENDONO, totaling 25 students. This research uses qualitative descriptive data analysis techniques to obtain data through observation methods, performance tests and interviews. The data obtained was analyzed and presented in qualitative descriptive form. Based on the research results, it was concluded that the application of learning mosaic artwork can increase students' creativity. It can be seen from the results of the students' mosaic work from the equipment, tools and materials, patterns produced using their imagination, attractive color compositions to produce beautiful mosaic works.